2017
DOI: 10.1038/srep43929
|View full text |Cite
|
Sign up to set email alerts
|

Response inhibition in Attention deficit disorder and neurofibromatosis type 1 – clinically similar, neurophysiologically different

Abstract: There are large overlaps in cognitive deficits occurring in attention deficit disorder (ADD) and neurodevelopmental disorders like neurofibromatosis type 1 (NF1). This overlap is mostly based on clinical measures and not on in-depth analyses of neuronal mechanisms. However, the consideration of such neuronal underpinnings is crucial when aiming to integrate measures that can lead to a better understanding of the underlying mechanisms. Inhibitory control deficits, for example, are a hallmark in ADD, but it is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 55 publications
3
11
1
Order By: Relevance
“…Indeed, executive functioning is associated with a large cerebral network with a preponderant role of the prefrontal cortex and its subcortical connections. These data echo recent studies that observed some differences in neurophysiological processes between adolescents with NF1 and controls in a Go/No-Go task (Bluschke, Von der Hagen, Papenhagen, Roessner, & Beste, 2017b). These findings should encourage future neurophysiological studies to focus on EF studies which will enrich our knowledge of this topic.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, executive functioning is associated with a large cerebral network with a preponderant role of the prefrontal cortex and its subcortical connections. These data echo recent studies that observed some differences in neurophysiological processes between adolescents with NF1 and controls in a Go/No-Go task (Bluschke, Von der Hagen, Papenhagen, Roessner, & Beste, 2017b). These findings should encourage future neurophysiological studies to focus on EF studies which will enrich our knowledge of this topic.…”
Section: Discussionsupporting
confidence: 90%
“…Clinically, precisely this slower response speed may be the main contributor to the observed attentional problems and ADHD-like symptoms frequently reported in patients with NF1 ( Kayl and Moore, 2000 , Mautner et al, 2015 , North et al, 1997 , Pride et al, 2012 ). In fact, we found a similar pattern of reduced reaction times and somewhat altered neurophysiological processing mechanisms in patients with NF1 in a GoNogo task ( Bluschke et al, in press ). Here we could show that, although there are clear similarities on the clinical level, neurophysiological processes clearly differ between patients with NF1 and those with ADHD.…”
Section: Discussionsupporting
confidence: 61%
“…On a neurobiological level, these deficits could be due to the deficient synthesis of dopamine on the one hand as well as due to other affected neurotransmitter systems relevant for learning on the other. Tying up with other data (Bluschke, von der Hagen, Papenhagen, Roessner, & Beste, 2017a, 2017b, the results show that despite the strong overlap in clinical phenotype and neuropsychological deficits in NF1 and ADHD, the underlying cognitive mechanisms are different. This is important to consider regarding pharmacological interventions in these diseases.…”
Section: Discussionsupporting
confidence: 51%